Analisis Tingkat Kepuasan Majalah Profile RRI Palembang berbasis Augmented Reality menggunakan framework COBIT 5 - Ninna Mugianti Utami, Tata Sutabri (Economics and Digital Business Review, 2023)
Magazine is a printed media that provides information needs by adding pictures which are arranged in an attractive manner. On the other hand, Augmented Reality is a technology that aims to combine digital content created by computers with the real world in real-time. Augmented Reality can be applied in almost all areas of life. One of them is in the entertainment sector. Delivery of information through writing and pictures in magazines and adding attractiveness by Augmented Reality. This is what supports the creation of the magazine and its Augmented Reality application. The profile magazine of RRI Palembang contains basic information about RRI Palembang which is presented with pictures from RRI Palembang. This magazine features an AR application that can be downloaded and run by each individual. The research method is divided into several stages, namely design, asset creation, implementation and testing. In the testing phase, it is divided into two, namely application testing by testing the functionality of the features provided by the application and testing respondents to determine the effectiveness of delivering information about RRI Palembang and the level of attractiveness of adding Augmented Reality features.